2016
DOI: 10.1038/srep34313
|View full text |Cite
|
Sign up to set email alerts
|

Negative Relationship between Erythropoietin Dose and Blood Lead Level in Patients Undergoing Maintenance Hemodialysis

Abstract: The adverse effects of increased blood lead levels have been well discussed. Several antioxidant agents have been reported to offer protection from lead toxicity and to reduce blood lead levels (BLL). Given that erythropoietin (EPO) also has antioxidant properties, the aim of this cross-sectional study was to assess the role of EPO and other clinical variables on BLL in hemodialysis (HD) patients. We recruited 931 maintenance hemodialysis (MHD) patients who had undergone HD for at least 6 months and who had ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Huang et al studied 931 patients receiving hemodialysis for at least six months and showed that serum lead level was high in 7% of the patients receiving EPO treatment, whereas, the serum leads level was high in 22% of patients who did not receive EPO treatment (20). In our study, no significant relationship between BLL and EPO dose was detected, which may be attributed to the smaller sample size.…”
Section: Discussioncontrasting
confidence: 72%
“…Huang et al studied 931 patients receiving hemodialysis for at least six months and showed that serum lead level was high in 7% of the patients receiving EPO treatment, whereas, the serum leads level was high in 22% of patients who did not receive EPO treatment (20). In our study, no significant relationship between BLL and EPO dose was detected, which may be attributed to the smaller sample size.…”
Section: Discussioncontrasting
confidence: 72%
“…All HCC patients 18 years old or older were enrolled in this study. Patients were excluded from this study if they had chronic kidney disease (stage 3, 4 or 5 [non-dialysis]) [ 2 ], other malignancies [ 17 ], lead [ 18 ] or cadmium [ 19 ] intoxication, had undergone renal transplantation in the previous 3 months, had undergone hemodialysis for less than 3 months, or had HCC before hemodialysis. As the International Agency for Research on Cancer lists lead and cadmium as Group 2B and 1 carcinogens, respectively [ 20 ], patients with lead and cadmium intoxication were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…This nding is in line with our results since, although not signi cantly, the weekly erythropoietin level was slightly greater in patients with hyperleadaemia (Table 1). This could be explained by the fact that lead intoxication is responsible for in ammation and oxidative stress (7), both of which are involved in resistance to EPO, as well as the association that hyperleadaemia may have with other EPO resistance factors, such as hyperparathyroidism, undernutrition and hypovitaminosis C; in this case, these conditions were signi cantly associated with hyperleadaemia in the present study, which could be explained, among other things, by its excessive consumption due to the oxidative stress generated by lead intoxication. In their study, Rahmat Pouresmaeil et al concluded that hyperleadaemia was associated with in ammation (CRP > 3 mg/l), malnutrition, iron de ciency and elevated parathyroid hormone levels in chronic haemodialysis patients (8).…”
Section: Discussionmentioning
confidence: 99%